FUNGSI dan KELEMAHAN UNIT OPERASI PELAYANAN DI BANDARA - Muhammad Resky; Juliater Simarmata (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2014)
Airport Operations Service Unit is spearheading the Airport Operations which in addition to its function, there are also weaknesses that in addition to the facilities and coordination problems, as well as human resources are less reliable and professional in his field. Operations Services unit is actually an image of the airport service from Soekarno-Hatta airport, especially in its performance.